Maybe we should - Foster, Melissa (Foster, Melissa. Silver Harbor, 2021)
"After spending years wondering who she was, tattoo artist Cait Weatherby finally found her answers on the sandy shores of Silver Island. With two half sisters she never knew existed, a group of friends she adores, and a devastatingly charming admirer who flirts with her at every turn, she's ready to figure out her next steps. The trouble is, Cait lives in the shadows of a dark past, and she can't afford complications that might cause her to lose the family she's only just found--complications like blue-eyed boatbuilder Brant Remington, who is as open as she is guarded. If only the sexy charmer would take the hint ... Brant is Cait's opposite in every way, but he's drawn to everything about the sexy newcomer from the quiet strength that rivals the caution in her mossy-green eyes to her tough facade that he can't wait to strip away. As Brant works his magic, Cait's walls come down. But as sweet as that feels, Cait knows how quickly good things can turn bad. It's going to take more than a little trust to beat the ghosts of her past and claim the future they both deserve"--